Gambaran Aktivitas Fisik Pada Individu Obesitas Di Wilayah Kerja Puskesmas Sidorejo Kidul Salatiga - Daniel Tri Angga (LPPM STIKES Guna Bangsa Yogyakarta, 2019)
Background: Obesity is one of the health problems related to the prevalence of cardiometabolic disease. WHO states that obesity is a complex, serious problem experienced by all age groups, ranging from children, adults to the elderly. Obesity must be treated immediately because it has the potential to become a health problem (1). In obese patients who have a Body Mass Index (BMI)> 30 kg / m2 will increase the risk of Coronary Heart Disease (CHD), both men and women. The American Heart Association (AHA) classifies obesity as a risk factor for coronary heart disease. Someone with central Obesity (upper body obesity) will be easily exposed to the risk of heart disease and other metabolic diseases known as metabolic syndrome compared with ginoid obesity (lower body obesity) is very small will be the risk of metabolic disease and coronary heart disease.